Escrow mechanism for personal security keys on IBE - ZOU Yue-peng1; OUYANG Dan-tong1; HE Li-li1; 2 (Tongxin xuebao)
A new escrow mechanism for personal security keys on IBE was proposed.This mechanism constructed a security trust system composed of private key generator, key management center, and user security component to set up a personal security key escrow model, thus providing identity validation, confidentiality and integrality check for the application, backup, recovery, and renewal of the escrowed keys.The mechanism, taking advantage of the IBE, simplified the process of authentication and encryption, mede it possible for users to complete independently the escrow of personal security keys.Therefore, it is more practical than traditional key escrow schemes.